Inhibitory activity of Enhydra fluctuans Lour. on calcium oxalate crystallisation through in silico and in vitro studies - Chattaraj, Bornika; Nandi, Arijit; Das, Anwesha; Sharma, Amit; Dey, Yadu Nandan; Kumar, Dharmendra; R, Mogana (Frontiers in Pharmacology, 2023)
The decoction of the whole plant of Enhydra fluctuans is used ethno medicinally by various tribes for the treatment of kidney stones and urinary problems. However, no scientific studies were carried out to delineate its influence on urinary stone formation and crystallisation. Hence, the present study is proposed to investigate the effect of the aqueous extract of Enhydra fluctuans extract on in vitro crystallisation of calcium oxalate. The present study also evaluated in silico studies of the metabolites with the target proteins present in the renal calcium oxalate stone matrix. The plant material was subjected to decoction to obtain an aqueous extract. The effect of the extract on calcium oxalate crystallization was evaluated by in vitro nucleation and aggregation assays. Further, the metabolites present in E. fluctuans were mined from the existing literature and their number was found to be 35. The selected 35 metabolites of E. fluctuans were subjected to molecular docking with the 5 proteins which are known to be responsible for calcium oxalate crystal growth. Results of in vitro studies indicated that the extract (50, 100, and 200 µg/ml) and standard drug cystone (1000 µg/ml) exhibited an inhibitory role in the nucleation process where the percentage inhibitions were 52.69, 43.47, 21.98, and 31.67 µg/ml respectively. The results of molecular docking studies revealed that 2 out of 35 metabolites i.e. Baicalein-7-O-diglucoside and 4',5,6,7-Tetrahydroxy-8-methoxy isoflavone-7-O-beta-D- galactopyranosyl-(1→3)-O-beta-D-xylopyranosyl-(1→4)- O-alpha-L-rhamnopyranoside showed modulatory effects on the four renal stone matrix-associated protein (Human CTP: Phosphoethanolamine Cytidylyltransferase (PDB ID: 3ELB), UDP glucose: glycoprotein glucosyltransferase 2 (Gene: UGGT2) (AlphaFold) and RIMS-binding protein 3A (Gene: RIMBP3) (AlphaFold), and Ras GTPase activating-like protein (PDB: 3FAY) based on their docking scores which indicates that they may inhibit the crystallization process. Findings from this study show that Enhydra fluctuans may be effective in the prevention of the crystallization of calcium oxalate. However, further, in vivo studies as well as molecular studies are needed to be conducted to confirm and strengthen its anti-urolithiatic activity and to elucidate the possible mechanism of action involved therein.